Augmented primary repair of patellar ligament rupture in three dogs - Smith, M. E. H.; de Haan, J. J.; Peck, J.; Madden, S. N. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
Treatment of unilateral patellar ligament rupture resulting from laceration is described in three large dogs. Surgical repair involved debridement and suturing of the ligament ends. Augmentation was provided with encircling loops of 27 kg test monofilament nylon passed through transverse holes drilled in the patella and proximal tibial tuberosity. All of the dogs returned to a pre-injury level of activity without any lameness being observed when they were reevaluated five to 24 months after their operation. The method described is a useful technique for repair of patellar ligament rupture that produced excellent and enduring results in these cases.
Keywords: Patellar ligament rupture; surgical repair; dog